Efetividade do Programa Nacional de Alimentação Escolar (PNAE) em tempos de pandemia: uma análise de dois municípios da região sudoeste paulista - Godoi, Ronaldo Wilson de (Universidade Federal de São Carlos, 2026)
This research encompasses an analysis of the effectiveness of the National School Feeding Program (PNAE) during the pandemic, considering the program's adaptation strategies in the face of the public calamity. It is a qualitative study conducted in two municipalities in the southwestern region of the State of São Paulo. Semi-structured interviews were carried out with program managers and nutritionists in the studied municipalities. Before the pandemic, while students were attending school and had proper access to school meals, the program strongly contributed to the development, growth, and personal performance of each student, fostering the formation of healthy eating habits. However, during the Covid-19 pandemic, a new scenario emerged, drastically affecting in-person education systems and students' access to school meals in public schools. After the gradual resumption of in-person classes in schools, students regained access to school meals. Despite the program adopting new adaptation strategies during the pandemic, beneficiary students still experienced a degree of food insecurity due to a lack of access to in-person school meals. Program managers and nutritionists took some initiatives during the COVID- 19 pandemic, such as providing food baskets, vegetables, and prepared meals, but these were insufficient to guarantee adequate nutrition, leading to losses in the quality of teaching and learning for students. This research highlighted the importance of managing the National School Feeding Program (PNAE) in the southwestern region of the state of São Paulo. Furthermore, it contributed to enabling nutritional managers of public policies to reflect on, adapt to, and develop effective strategies for implementing food security policies, whether in optimistic or pessimistic scenarios.
Effectiveness of the National School Feeding Program (PNAE) in times of pandemic: an analysis of two municipalities in the southwest region of São Paulo
Eficacia del Programa Nacional de Alimentación Escolar (PNAE) en tiempos de pandemia: un análisis de dos municipios de la región suroeste de São Paulo
Keywords: Programa Nacional de Alimentação Escolar; Efetividade; Segurança alimentar; Pandemia; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; CIENCIAS SOCIAIS APLICADAS; CIENCIAS HUMANAS; 1. Erradicação da Pobreza; 2. Fome Zero e Agricultura Sustentável; 3. Saúde e Bem-Estar; 4. Educação de Qualidade